Tingkat Keterampilan Dasar Pencak Silat Peserta Ekstrakurikuler Pencak Silat SMK Ma’arif NU 1 Bener - Sutopo, Wisnu Guntur (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
The unknown level of the basic skills of pencak silat students participating in extracurricular pencak silat at SMK Ma'arif Nahdltul Ulama 1 Bener has an impact on the improper arrangement of the training program. The absence of regular evaluations and the frequency of training that does not affect the basic skill level of the students participating in the extracurricular pencak silat at SMK Ma'arif Nahdlatul Ulama 1 Bener. This study aims to determine the level of basic skills of pencak silat students participating in extracurricular pencak silat at SMK Ma'arif Nahdlatul Ulama 1 Bener. The method used in this research is a survey with test and measurement techniques. The subjects of this study were students participating in the extracurricular pencak silat at SMK Ma'arif Nahdlatul Ulama 1 Bener, totaling 16 students. The instrument used is an instrument composed by Drs. Agung Nugroho AM., M. Si. Analysis of the data used to describe the results of the research is descriptive percentage. The results showed that the level of basic skills of pencak silat extracurricular pencak silat students at SMK Ma'arif Nahdlatul Ulama 1 Bener 0 students (0%) in the very good category, 0 students (0%) in the good category, 0 students (0%) in the excellent category. moderate, 1 student (6.25%) in the poor category, and 15 students (93.75%) in the very poor category.Keywords: skills, pencak silat, students, extracurricular